Drug delivery using theranostics: An overview of its use, advantages and safety assessment - Chiari-Andréo, Bruna Galdorfini [UNESP]; Abuçafy, Marina Paiva [UNESP]; Manaia, Eloísa Berbel [UNESP]; da Silva, Bruna Lallo [UNESP]; Rissi, Nathalia Cristina [UNESP]; Oshiro-Júnior, João Augusto [UNESP]; Chiavacci, Leila Aparecida [UNESP] (Bentham Science Publishers, 2020)
Following progress in modern medicine, advances have been made in diagnosis and treatment tools. Multifunctional nanomaterials that combine therapeutic and diagnostic functions in a single nanostructured complex are known as ‘theranostics’. To obtain a theranostic, a single particle, usually a nanoparticle, is manufactured to contain a therapeutic element (such as a drug) coupled with an imaging element. There are many kinds of nanoparticles available today that can be used to obtain theranostics, such as liposomes, cyclodextrin, conjugates and complexes, dendrimers, vesicles, micelles, core-shell particles, microbubbles, and carbon nanotubes. Because these materials interact with and should have effects on biological systems, their use may overcome health challenges. Considering the novelty and importance of this subject, this review aims to present general information about theranostics and discuss the safety and presumable toxicity of these constructs. In addition, we describe the methodologies that can be used to assess the safety of theranostics. This review is based on a literature search on theranostics, using the Web of Science, PubMed and Science Direct as the main sources of information. The period of publication was not delimited due to the scarcity of information and publications on this topic. Although many promising theranostic systems have been investigated and may revolutionise therapy, when designing new tools, researchers need to find alternatives to minimise their toxicity. The study of the toxicology and biocompatibility of theranostics needs to be continued, including clinical studies, with the aim of benefitting many patients in the future.
Keywords: Diagnosis; Safety; Targeting; Theranostic; Therapeutics; Toxicity